The luxury value perception: Malaysian emotional intelligence towards purchase intention / Arunnaa a/p Sivapathy and Safwan Marwin Abdul Murad - Arunnaa, Sivapathy; Safwan Marwin, Abdul Murad (Universiti Teknologi MARA, Kedah, 2021)
The research will investigate the intention of purchasing behaviour of Malaysian consumers using TPB variables known as the attitudes, subjective norms and perceived behavioural control. The conceptual mode l will be moderated by emotional intelligence and will examine the effect of the luxury values towards the Malaysian consumers' purchase intention. The model used Wiedmann (2007) framework. This research needed a comprehension investigation in Malaysia as a developing country. The results of the research would help the luxury marketers to plan, improve and execute the marketing and communicating strategy in Malaysia. This study also offers a broad literature of the four luxury values of the Malaysian customers towards luxury products.